The Effect of Gross Profit, Operating Profit, and Net Profit in Predicting Future Cash Flows - Pratiwi, Suryaningtyas Gusti; Sukesti, Fatmasari; Hanum, Ayu Noviani (Economics and Business International Conference Proceeding, 2024)
This study was conducted to determine gross profit, operating profit and net profit to cash flow in manufacturing companies in the consumption sector listed on the Indonesia Stock Exchange in 2017-2022. In this study, the sampling technique used is non-probability sampling with the technique taken, namely purposive sampling. The population in this study is all Manufacturing Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange in 2017 – 2022. The results of the F test were obtained from the three variables simultaneously on cash flow with a significance of 0.003 where the three variables of Gross Profit, Net Profit and Operating Profit simultaneously had a positive effect on cash flow in the future.